Spectral Efficient and Reliable Irregular QC-LDPC Channel Coding Scheme for 5G Vehicular Applications - Arora, Komal; Singh, Jaswinder; Randhawa, Yogeshwar S. (International Journal of Sensors Wireless Communications and Control, 2020)
Background and Objective: Today’s wireless systems i.e. 4G systems are facing major issues of spectral inefficiency, and unreliability for high speed applications. To address these issues, 5G systems have chosen LDPC codes and replaced earlier used Turbo Codes for the purpose of Channel encoding. This paper proposes a design method for Irregular QC- LDPC codes with better spectral efficiency and reliability that too at higher speed. Methods: This paper describes the analysis of LDPC codes and their comparison with different encoding techniques. Also, it describes the design method for Irregular QC- LDPC codes and elaborates its applications in high-pace vehicular 5G scenario. Conclusion: This paper focuses on the design method for irregular QC-LDPC codes and using MATLAB simulations illustrated that these codes have better reliability and spectral efficiency as compared with conventional LDPC codes in high-speed environments.
Keywords: 5G